2020
DOI: 10.7717/peerj.8820
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific differences in gait domains and global cognitive function in older women: gait characteristics based on gait speed modification

Abstract: Background Several studies have reported the association between gait and global cognitive function; however, there is no study explaining the age-specific gait characteristics of older women and association between those characteristics and global cognitive function by age-specific differences and gait speed modification. The aim of this study was to examine age-specific differences in gait characteristics and global cognitive function in older women as well as identify gait domains strongly associated with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 45 publications
(56 reference statements)
5
37
0
Order By: Relevance
“…It has also been reported that gait speed, muscle mass, and sarcopenia are strongly associated with functional capacity [ 17 , 18 , 19 ]. However, our study expands this finding by showing that sarcopenia is not just a predictor, but also an important mediator of the effect of an exercise program on another important factor for the health such as CRF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that gait speed, muscle mass, and sarcopenia are strongly associated with functional capacity [ 17 , 18 , 19 ]. However, our study expands this finding by showing that sarcopenia is not just a predictor, but also an important mediator of the effect of an exercise program on another important factor for the health such as CRF.…”
Section: Discussionmentioning
confidence: 99%
“…The EWGSOP suggests the gait speed test as an easy and valid method for assessing physical performance [ 3 , 15 , 16 ]. Gait speed has been performed to evaluate various health-related factors such as physical functions, health status [ 17 , 18 , 19 ], and quality of life [ 20 ]. A well-known meta-analysis of 2888 older people set the minimum health threshold for gait speed at ≥ 0.8 m/s [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Shapiro-Wilk test was used to determine whether data were normally distributed. To verify slower and faster speed estimations, an ICC (2,1) analysis assessed the reliability of the estimated and measured speeds, as previously described by Noh et al [19]. Estimated speed was defined as the calculated speed based on the measured preferred walking speed.…”
Section: Discussionmentioning
confidence: 99%
“…An experimental operator explained the estimated walking speeds to participants before each trial. Participants were instructed to perform the overground walking test at speeds as close as possible to the targeted walking speeds, as described previously [19]. Although real stepping rhythms and measured metronome beats may not have demonstrated perfect agreement, we attempted to control the accuracy of each participants' performance as much as possible.…”
Section: Test Proceduresmentioning
confidence: 99%
“…Everybody has his/her own desired walking speed. It is influenced by many factors such as intention outlook, age, and gender [13,28,29,32]. We have used Gaussian distribution model, which offers a normal distribution pattern similar to real-world scenarios.…”
Section: Social Force Modelmentioning
confidence: 99%